Peran Mahasiswa Kelautan Perikanan dalam Program Internship Budidaya Hotate di Hotate Business Fishery Cooperative Association di Jepang - Imron Nastir; Eny Triastuti (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to explore the role of marine fisheries students in the hotate aquaculture internship program at the Hotate Business Fishery Cooperative Association in Japan. This internship program is designed to provide practical experience and in-depth knowledge of the hotate aquaculture industry, one of the important fisheries sectors in Japan, especially in Hokkaido. Students who participate in this program are directly involved in various aspects of hotate cultivation, including seed selection, environmental maintenance, catching, processing, and distribution. This study uses a qualitative method with in-depth interviews and participatory observation to collect data from participating students, mentors, and program managers. The results of the study showed that participation in the internship program provided significant benefits for students, including improved technical skills, an understanding of best practices in hotate farming, and the ability to adapt to modern technologies and methods in the fishing industry. In addition, the program also strengthens the relationship between educational institutions and industry, as well as opens up career opportunities for students in the global fisheries sector.This study concludes that the internship program at the Hotate Business Fishery Cooperative Association has an important role in developing quality and competitive human resources in the fishing industry, as well as contributing to sustainability and innovation in hotate cultivation in Japan.